Recent Advances on DNAzyme-Based Biosensors for Detection of Uranyl - Bai, Yunlong; Xu, Lechang; Chai, Huining; Zhou, Lei; Jiang, Guoping; Zhang, Guangyao (Frontiers in Chemistry, 2022)
Nuclear facilities are widely used in fields such as national defense, industry, scientific research, and medicine, which play a huge role in military and civilian use. However, in the process of widespread application of nuclear technology, uranium and its compounds with high carcinogenic and biologically toxic cause a lot of environmental problems, such as pollutions of water, atmosphere, soil or ecosystem. Bioensors with sensitivity and specificity for detection of uranium are highly demand. Nucleic acid enzymes (DNAzyme) with merits of high sensitivity and selectivity for targets as excellent molecular recognition elements are commonly used for uranium sensor development. In this perspective review, we summarize DNAzyme-based biosensors for the quantitative detection of uranyl ions by integrating with diverse signal outputting strategies, such as fluorescent, colorimetry, surface-enhanced Raman scattering and electrochemistry. Different design methods, limit of detection, and practical applications are fully discussed. Finally, the challenges, potential solutions and future prospects of such DNAzyme-based sensors are also presented.